Immortal Glory and the Problem of Death in Romans 3.23 - Blackwell, Ben C. (Journal for the study of the New Testament, 2010)
Paul enigmatically describes humanity’s universal sinfulness in Rom. 3.23 as a lack of ‘the glory of God’. Interpreters have tried to situate the lack of this glory in various contexts: ancient honour discourse, ancient Jewish Adam traditions, and Paul’s ethical discourse. To interpret this passage, this article utilizes the literary context of glory language throughout the letter. From this we find that glory denotes not only elevated honour, but also incorruption. Thus, the lack of glory in 3.23 refers to mortality and shame as the result of sin. In addition, this study of glory has implications for the burgeoning interest into the question of theosis with regard to Pauline theology.